Maskless functionalization of a carbon nanotube dot array biosensor using an ultrafine atmospheric pressure plasma jet. (August 2015) - Abuzairi, Tomy; Okada, Mitsuru; Mochizuki, Yohei; Poespawati, Nji Raden; Purnamaningsih, Retno Wigajatri; Nagatsu, Masaaki
Abstract: To realize maskless functionalization of a carbon nanotubes (CNTs) dot array, a localized surface functionalization technology using an ultrafine atmospheric pressure plasma jet was developed. The plasma surface functionalization onto vertically aligned CNTs was carried out in two stages: pretreatment for activation of the CNT surface and posttreatment for surface functionalization. The experimental results of chemical derivatization with the fluorescent dye show that the CNT dot array was not only successfully functionalized with amino (–NH2 ) and carboxyl (–COOH) groups but also functionalized without any interference between functional groups. The success of maskless functionalization in the line pattern provides a means of a multifunctionalized CNT dot array with direct implications for future application of a microarray biosensor.